TiO2 photocatalysis of naproxen : effect of the water matrix, anions and diclofenac on degradation rates - Devagi, Kanakaraju; Motti, Cherie A.; Glass, Beverley D.; Oelgemöller, Michael (Elsevier Ltd, 2015)
The TiO2 photocatalytic degradation of the active pharmaceutical ingredient (API) naproxen (NPX) has been studied using a laboratory-scale photoreactor equipped with a medium pressure mercury lamp. UV/TiO2 photocatalysis proved highly efficient in the elimination of NPX from a variety of water matrices, including distilled water, unfiltered river water and drinking water, although the rate of reaction was not always proportional to TiO2 concentration. However, the NPX degradation rate, which follows first-order kinetics, was appreciably reduced in river water spiked with phosphate and chloride ions, a dual anion system. Addition of chloride into drinking water enhanced the TiO2-photocatalysed degradation rate. Competitive degradation studies also revealed that the NPX degradation was greatly reduced in the presence of increased concentrations of another API, diclofenac (DCF). This was established by (i) the extent of mineralization, as determined by dissolved organic carbon (DOC) content, and (ii) the formation of intermediate NPX by-products, identified using liquid chromatography and electrospray ionization (positive and negative mode) mass spectrometry techniques. This study demonstrates that competition for active sites (anions or DCF) and formation of multiple photoproducts resulting from synergistic interactions (between both APIs) are key to the TiO2-photocatalysed NPX degradation.